Anatomical Study of Vagal Trunks at Gastro Esophageal Junction - Dr. Jamuna Meenakshisundaram2, Dr. Amudha Govindarajan (International Journal of Innovative Research in Medical Science, 2016)
Vagus is the chief parasympathetic nerve to the most of the organs in the neck, thorax and abdomen. The number and position of anterior and posterior vagal trunks have variations at the gastro esophageal junction. This is a very important factor for surgeons who plan for vagotomy or vagal preservation surgeries in esophageal resection. The study was done in 45 autopsy specimens. Considerable variations were found in the number and position of anterior and posterior vagal trunks. Knowledge about these variations will be helpful for surgeons to avoid injury to the vagus nerve in hiatal hernia surgeries and in lower esophageal resection.